The effect of economic policy uncertainty on the risk of falling stock prices (Case study: companies listed on the Tehran Stock Exchange) - Ali Pazhooyan; Kobra Meskini (New Applied Studies in Management, Economics & Accounting, 2020)
This article examines the effect of economic policy uncertainty on the risk of stock price falls in companies listed on the Tehran Stock Exchange. To measure the uncertainty of economic policy, indicators of economic growth and exchange rates have been used, and to measure the variable risk of stock price falls, two methods of high and low fluctuations and negative skewness of monthly stock returns have been applied. This research is empirical and descriptive-correlation. in order to analyse the data and extract the research results, Excel, stata14 and Eviwse10 software were used and 123 companies were selected as sample to test the hypotheses during the period 2013-2018. The results show that economic growth has no significant relationship with positive and negative fluctuations, the foreign exchange rate has a positive and significant relationship with high and low fluctuations. On the other hand, economic growth has a positive and significant relationship with negative stock returns and foreign exchange rate has a negative and significant relationship with negative skewness stock returns. Also, the results in the present study show that the coefficient of state ownership in economic growth does not have a significant relationship with high and low fluctuations. The coefficient of state ownership in the exchange rate has a negative and significant relationship with high and low fluctuations.